Introduction to comparative politics : political challenges and changing agendas - Kesselman, Mark; Krieger, Joel ; ;Joseph, William A. (Boston, Massachusetts : Cengage Learning Asia Pte Ltd, 2016)
Updated to reflect today's political climate, the seventh edition of INTRODUCTION TO COMPARATIVE POLITICS offers a country-by-country approach that allows students to fully examine similarities and differences among countries and within and between political systems. Each chapter offers an analysis of political challenges and changing agendas within countries and provides detailed descriptions and analyses of the politics of individual countries. The text offers a condensed narrative and student-friendly pedagogy, such as marginal key terms and questions that will help them make meaningful connections and comparisons about the countries presented. This edition consists of 13 country case studies, as well as a case study on the European Union, providing an interesting sample of political regimes, levels of economic development, and geographic regions.
Part I. Introduction -- Part II. Consolidated democracies -- Part III. Mixed systems -- Part IV. Authoritarian regimes.
Includes bibliographical references and index.
Keywords: COMPARATIVE GOVERNMENT